Staining methods applied to glycol methacrylate embedded tissue sections - Cerri, Paulo Sérgio [UNESP]; Sasso-Cerri, E. (Elsevier B.V., 2003)
The use of glycol methacrylate (GMA) avoids some technical artifacts, which are usually observed in paraffin-embedded sections, providing good morphological resolution. on the other hand, weak staining have been mentioned during the use of different methods in plastic sections. In the present study, changes in the histological staining procedures have been assayed during the use of staining and histochemical methods in different GMA-embedded tissues.Samples of tongue, submandibular and sublingual glands, cartilage, portions of respiratory tract and nervous ganglion were fixed in 4% formaldehyde and embedded in glycol methacrylate. The sections of tongue and nervous ganglion were stained by H&E. Picrosirius, Toluidine Blue and Sudan Black B methods were applied, respectively, for identification of collagen fibers in submandibular gland, sulfated glycosaminoglycans in cartilage (metachromasia) and myelin lipids in nervous ganglion. Periodic Acid-Schiff (PAS) method was used for detection of glycoconjugates in submandibular gland and cartilage while AB/PAS combined methods were applied for detection of mucins in the respiratory tract. In addition, a combination of Alcian Blue (AB) and Picrosirius methods was also assayed in the sublingual gland sections.The GMA-embedded tissue sections showed an optimal morphological integrity and were favorable to the staining methods employed in the present study. In the sections of tongue and nervous ganglion, a good contrast of basophilic and acidophilic structures was obtained by H&E. An intense eosinophilia was observed either in the striated muscle fibers or in the myelin sheaths in which the lipids were preserved and revealed by Sudan Black B. In the cartilage matrix, a strong metachromasia was revealed by Toluidine Blue in the negatively-charged glycosaminoglycans. In the chondrocytes, glycogen granules were intensely positive to PAS method. Extracellular glycoproteins were also PAS positive in the basal membrane and in the region occupied by the lamina externa and reticular fibers surrounding each smooth muscle cells of the blood vessels. In the epithelial cells of the respiratory tract, acid and neutral mucins were histochemically detected by AB and PAS methods, respectively. Moreover, granules containing acid and neutral mucins were revealed in purple by AB and PAS concomitantly. In the sublingual gland sections, a distinct affinity of acid mucins by AB (in turquoise-blue) and collagen fibers by Picrosirius (in red) was obtained when these methods were combined. Although some routine dyes used in paraffin sections have showed a weak stain in historesin sections, our results showed that different dyes could be applied in GMA sections if modified staining procedures were assayed. Therefore, appropriate staining contrast and, thus, detection of one or different substances in a same section can be acquired in association to the good morphological resolution provided by GMA. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: glycol methacrylate; morphology; histochemistry; staining methods; H&E; picrosirius; alcian Blue/Periodic acid-schiff; sudan BlackB